1983
DOI: 10.1139/v83-448
|View full text |Cite
|
Sign up to set email alerts
|

The use of shift reagents and 13C nuclear magnetic resonance for assignment of stereochemistry to oximes

Abstract: The effects of the shift reagents Eu(dpm), and Eu(fod), on the 'H and "C nmr spectra of twelve oximes of diverse structure were examined. The proton data show that the use of proton shifts to assign oxime stereochemistry, as has been done in the past, is unreliable. In contrast, Eu(dpm), causes LIS values for the "C signals of a carbons which are strongly dependent on stereochemistry. Signals for all a carbons anti to the oxime oxygen experience large downfield shifts while all syrl carbons are either unaffect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Finally, a heteronuclear 2D J -resolved NMR experiment was used in order to determine 1 J CH coupling constants throughout the series of aldoximes. It is well established from previous studies that there is a large and constant difference between the magnitudes of 1 J CH coupling constants of the iminyl moiety in syn - anti isomers [ 39 ], which is larger by at least 10–15 Hz for the syn isomer. The measurements of compounds 4a – c showed that the relevant 1 J CH coupling constants of the iminyl moiety were around 175.0 Hz for the predominant syn isomer, while the minor anti isomer provided significantly lower coupling constant values by around 13.0 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a heteronuclear 2D J -resolved NMR experiment was used in order to determine 1 J CH coupling constants throughout the series of aldoximes. It is well established from previous studies that there is a large and constant difference between the magnitudes of 1 J CH coupling constants of the iminyl moiety in syn - anti isomers [ 39 ], which is larger by at least 10–15 Hz for the syn isomer. The measurements of compounds 4a – c showed that the relevant 1 J CH coupling constants of the iminyl moiety were around 175.0 Hz for the predominant syn isomer, while the minor anti isomer provided significantly lower coupling constant values by around 13.0 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift differences between H-6eq and H-6ax are unusually large (¾1 ppm) and also, with the exception of the axial proton for the cis series, they are easily identified in the spectra, providing an excellent probe for the determination of these equilibria. Figure 6 presents the HETCOR spectrum of a mixture of the E and Z isomers of the 2-chlorocyclohexanone Omethyl oxime (10). It can be seen that the C-6 signal for the E isomer at 20.6 ppm couples with two different protons, showing that the protons cis and trans to the chlorine atom have different chemical shifts.…”
Section: Axial/equatorial Populationsmentioning
confidence: 99%
“…The deshielding effect of the oxime oxygen on the neighboring proton provides an easy method to determine E/Z populations, through integration of signals arising from the syn and anti protons. 9,10 The carbon syn to the OH or OMe groups is shielded and can be a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fraser et a1., 26 Eu(DPM), causes a large induced shift for the c~-'~C signal, and this is strongly dependent Proton chemical shift changes in the presence of Eu(DPM), have been found to be an unreliable indicator of oxime stereochemistry. 26 In this study Eu(DPM), was found to cause a large downfield shift in the C-1 resonance position and a negligible shift for that of C-3. This result confirms that the oxime hydroxyl is located anti to c-1.…”
Section: ~ ~~ ~~mentioning
confidence: 99%